Identification and characterizationof micro-RNA in Macrobrachium rosenbergii / Tan Tian Tian - Tan, Tian Tian (2012)
MicroRNAs are ~20-22nt non protein-coding RNA regulatory genes that posttranscriptionally regulate many protein–coding genes to influence critical biological and metabolic processes. While the number of known microRNA is increasing, there is no published data for microRNA in freshwater prawns (Macrobrachium rosenbergii) a commercially cultured and economically important food species. Through deep parallel sequencing and an in silico data analysis approach, 327 miRNA families have been identified from small RNA libraries with reference to both the de novo transcriptome of M.rosenbergii obtained from RNA-Seq and to miRBase (Release 18.0, November 2011). Based on the identified mature miRNA and recovered precursor sequences that form appropriate hairpin structures, three conserved miRNA (miR125, miR750, miR993) and 27 novel miRNA candidates encoding messenger-like non-coding RNA have been identified. miR-125, miR-750, G-m0002/H-m0009, G-m0005, G-m0008/H-m0016, Gm0011/ H-m0027 and G-m0015 were selected for experimental validation with stemloop quantitative RT-PCR and were found coherent with the expression profile of deep sequencing data as evaluated with Pearson’s correlation coefficient (r = 0.835178 for miRNA in gill, r = 0.724131 for miRNA in hepatopancreas). Using a combinatorial approach of pathway enrichment analysis and inverse expression relationship of miRNA and mRNA, four co-expressed novel miRNA candidates (G-m0005, G-m0008/H-m0016, G-m0011/H-m0027, and G-m0015) were found to be associated with energy metabolism. In addition, the expression of the three novel miRNA candidates (G-m0005, G-m0008/H-m0016, and G-m0011/H-m0027) were also found to be significantly reduced at the 9 and 24 hours post infection in a controlled experiment of M.rosenbergii challenged with infectious hypodermal and haematopoietic necrosis virus. These findings provide a reference point to further improving the understanding of the repertoire of crustacean miRNAs.